Sharia Rural Banks in East Java: How Its Hazard Rate? (The Analysis Using Multiple Period Logit) - Oktaviana, Ulfi Kartika; Miranti, Titis (Al-Tijary, 2022)
Sharia Rural Banks in East Java provide essential financial services in compliance with Islamic law, fostering economic growth in rural communities. Assessing their hazard rate, which indicates the probability of bank failure over time, is crucial for understanding their stability and resilience amidst various economic and regulatory challenges. Therefore, this study aimed to determine the susceptibility opportunities of each BPRS. The second objective is to find out the financial ratios that cause it. The financial sustainability measure is a measuring tool to calculate the chance of survival. Financial sustainability approximates the value of Financial Self-Sufficiency (FSS). The population used is BPRS in East Java. The analysis technique used survival analysis and multiple period logit models Research variables that invariably affect the sustainability of BPRS include NPF, ROA, Bank Size, PM, FR, GLP, WoR, and LDR. The study on Sharia Rural Banks (BPRS) in East Java reveals that only about 30% of these banks have a stable financial condition, indicating a low overall sustainability rate. This suggests that the majority of BPRS need to improve their financial health to better support regional economic development and the growth of MSMEs.